Physiological changes and full-length transcriptome of Artemisia sphaerocephala in response to drought stress - Shasha Xiao; Yuhua Ma; Jingwen Hao; Guisheng Ye; Dan Zhang; Jiawei Dong; Mingming Zhao; Nanxiang Yang; Xiaowei Wang (BMC Plant Biology)
Abstract Background Artemisia sphaerocephala is an important sand-fixing plant in arid sandy areas. To elucidate the physiological and molecular changes of A. sphaerocephalala induced by drought stress, this study used a combination of second-generation sequencing and third-generation sequencing technologies to sequence the full-length transcriptome. The sequencing results can identify significant genes and main pathways related to drought resistance of A. sphaerocephalala. Results Changes in physiological characteristics indicated that the relative permeability of plasma (RPP), superoxide dismutase (SOD) activity, peroxidase (POD) activity, catalase (CAT) activity, malondialdehyde (MDA), proline (Pro), soluble sugar (SS), soluble protein (SP) contents increased under drought stress, and all of them decreased sharply after re-watering. The relative water content (RWC) exhibited a declining trend under drought stress, but it increased after re-watering and the chlorophyll content showed a continuous decrease under drought stress and re-watering. Additionally, transcriptome sequencing revealed that important metabolic pathways, such as Plant hormone signal transduction, Starch and sucrose metabolism, Glyoxylate and dicarboxylate metabolism, and Nitrogen metabolism were enriched in A. sphaerocephala under severe drought stress. Moreover, the RNA-Seq results of 10 genes were confirmed by real-time PCR, and the results showed that all of them were involved in the process of drought stress adaptation of A. sphaerocephala. Conclusions This is the first reported large-scale sequencing of the full-length transcriptome of A. sphaerocephala under drought stress, and these results will provide a better understanding of A. sphaerocephala responses to drought stress and lay the groundwork for analysing the expression profile of genes related to drought tolerance in plants.